2012
DOI: 10.2141/jpsa.011109
|View full text |Cite
|
Sign up to set email alerts
|

Leg Weakness Pathology in Broiler Chickens

Abstract: The aim of the present work is to make a review on the literature concerning the incidence of some major pathologies of leg skeleton in broiler chickens and broiler breeders, related to poor animal welfare. On the basis of data on the incidence of leg skeletal pathology published by us and by other researchers, this review goes through some reports on femoral head necrosis (FHN), tibial dyschondroplasia (TD), rupture of the gastrocnemius tendon (RGT) and rickets. The welfare of broiler chickens and breeder flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
(60 reference statements)
0
19
0
1
Order By: Relevance
“…In addition, the 364 reason for a higher DOA % related to trauma in the normal-mortality group needs 365 further investigation in the future. It has been reported that birds with heavy tibial 366 dyschondroplasia (TD) are predisposed to fractures during catching and 367 transportation (Dinev, 2012). However, none of the broilers in our study exhibited TD 368 along with fractures or hemorrhages.…”
mentioning
confidence: 59%
“…In addition, the 364 reason for a higher DOA % related to trauma in the normal-mortality group needs 365 further investigation in the future. It has been reported that birds with heavy tibial 366 dyschondroplasia (TD) are predisposed to fractures during catching and 367 transportation (Dinev, 2012). However, none of the broilers in our study exhibited TD 368 along with fractures or hemorrhages.…”
mentioning
confidence: 59%
“…At slaughter age, leg problems (pathologies that re sult in impaired walking ability), such as tibial dyschondroplasia, rickets, and femoral head necrosis, are highly prevalent in broiler chickens (reviewed by Dinev, 2012). These leg problems constitute a welfare problem and result in economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…These include a number of cases related to deficiency or infectious etiology, as well as specific forms of rickets, femoral head necrosis, rupture of the gastrocnemius tendon (Dinev, 2008(Dinev, , 2009(Dinev, , 2012. Data on axial skeleton abnormalities, mostly spondylolisthesis and scoliosis, which could be asymptomatic, can be found in separate reports.…”
Section: Introductionmentioning
confidence: 99%